Follow the Money Through Apple Pay (Journal of The Colloquium for Information Systems Security Education, 2020)
Rapid growth in the number of mobile phones and their users has brought ecommerce applications and mobile payments to the forefront along with raising significant new cybersecurity concerns. Consumer enthusiasm for “tap-and-go” purchases must be tempered with knowledge about new risks and responsibilities that come along with these payment technologies. This paper highlights and analyzes key risks within end-to-end mobile-payment transactions through the lens of one of the most popular services: Apple Pay. Hackers are relentlessly adapting their ploys to breach these payment systems. Proactive approaches are identified to better secure vulnerabilities in smartphones, networks, communication, consumers, merchants and banks, along with practical, proactive countermeasure and action plans.
Keywords: apple pay; mobile commerce; mcommerce; near field; communication; NFC